The role of e-service quality management in the delivery business value - Mahani Mohammad, Abdu Shakur; Doherty, Neil F.; Ellis-Chadwick, Fiona (Elsevier Science, Ltd., 2015)
In sharp contrast to the extensive debate that has been conducted in the contemporary literature, with regard to consumers' perceptions of e-service quality, the voice of those managing e-service quality has remained relatively silent. Against this backdrop, the primary aim of the research presented in this paper is to address the gap in the literature with regard to the role of electronic service quality management in leveraging business value from on-line retailing strategies. The study was undertaken using a quantitative research methodology, based upon questionnaires, which resulted in a sample of 225 responses, completed by senior managers from across the UK's on-line retail sector. The results of the statistical analyses have demonstrated that the perceived success of a retailer's e-commerce operations is strongly associated with both the management approaches to e-service quality and the level of e-commerce adoption. Of particular interest is our finding that as the scale and scope of a retailer's e-commerce operations grow, there is a concomitant need for its e-service quality operations to develop, if it is to realise the full value from its on-line activities. The article adds to the body of knowledge regarding the management of electronic service quality while also seeking to stimulate critical debate concerning the role of service quality practises within prevailing IT value discourses.